Knowledge of Sexual and Reproductive Health Among High School Students, Batam, Indonesia - Risqi Utami; Arya Ramadia; Angga Putri; Datuk Munirah; Tukimim Sansuwito (Institute of Computer Science (IOCS), 2022)
This study aims to describe sexual knowledge and reproductive health among school-going adolescents and compare levels of knowledge between males and females. A cross-sectional study was conducted on 387 high school adolescents using a self-validated questionnaire. Adolescents' knowledge level is high at 39.14%, the moderate category is 50.55%, and low-level knowledge is 10.31%. An independent t-test revealed that the average knowledge score of men and women showed no significant difference, with a mean score of 12.42 for males and 12.37 for females. The majority of adolescents discussing sexual matters with friends is 43.41%, 98.71% of adolescents ever heard about contraception, 89.66% know condoms as contraception, and 24.55% do not know how to use them. As many as 51.68% of adolescents only know that HIV/AIDS is a sexually transmitted disease. Lack of knowledge of important aspects of sexual and reproductive health insurance and the need to strengthen sexual and reproductive health education.